On the Mechanisms of Characterization Through Literary Allusion - Girunyan, Gayane (Armenian Folia Anglistika, 2008)
As a complex sign with inter-textual ontology, literary allusion reveals its full interpretative potential when it serves for characterization. The material which has undergone extensive analysis makes it possible to distinguish between three basic types of description through allusion – direct, indirect and hybrid.